The Clinical Efficacy of Clopidogrel Bisulfate Tablets Combined with Olmesartan Medoxomil for Ischemic Stroke with Hypertension and the Effect of Angiotensin II Type 1 Receptor Level on Prognosis - Jia Yu (Hindawi Limited, 2021)
Background. Ischemic stroke combined with hypertension can increase risks of stroke recurrence and death. Aim. The aim of this study is to investigate the clinical efficacy of clopidogrel bisulfate tablets combined with olmesartan medoxomil in the treatment of ischemic stroke patients with hypertension and the effect of angiotensin II type 1 receptor (AT1R) level on prognosis. Methods. Ninety ischemic stroke patients with hypertension were chosen for continuous treatment with clopidogrel bisulfate tablets and olmesartan medoxomil for 12 months. The Modified Edinburgh Scandinavian Stroke Scale (MESSS) score, Brunnstrom score, Barthel score, death, recurrence, and progression of cerebrovascular residual lesions were observed and recorded during the treatment period. According to the plasma AT1R expression of the patients before treatment, the patients were divided into a high-AT1R group and low-AT1R group. Then, survival analysis was performed. Results. Compared with pretreatment, the MESSS scores of the patients at the first, second, third, sixth, ninth, and twelfth months after treatment were reduced (p<0.01) while the Brunnstrom score and Barthel score were prominently boosted (p<0.01). Compared with the low-AT1R group, patients in the high-AT1R group had higher rates of stroke recurrence and progression of residual cerebrovascular lesions (p<0.05). Conclusion. Clopidogrel bisulfate tablets combined with olmesartan medoxomil has prominent clinical effects in the treatment of ischemic stroke patients with hypertension, evidently improving the prognosis. In addition, the level of AT1R may be a vital factor affecting the prognosis.